AROUND SELECTED ISSUES OF PROFESSIONAL ACTIVITY OF DISABLED PEOPLE (Research Bulletins of the Faculty of Economic Sciences, 2022)
This article is devoted to selected issues of professional activity of people with disabilities. The aim of this article is to present selected needs and problems of people with various types of disabilities in the context of their professional activity. The article focuses on the issue of disability. The attention was paid to the important role that professional activity plays in the life of a person with disabilities. The genesis of problems with regard to the problem of employment of people with disabilities, as well as the consequences of professional inactivity are presented. The available forms of employment for people with disabilities on the open labor market are presented, as well as the specificity of selected needs of people struggling with various types of disability in the context of their professional activity. Examples of activities aimed at improving the satisfaction of professional needs of people with disabilities were also presented. A research report was presented on the needs of people with disabilities in terms of professional activity in the context of various types of disability.
Keywords: distability, professional activity, needa, problems